-429 T/C and -374 T/A Polymorphisms in Receptor Advanced Glycation Endproducts (RAGE) gene in Type 2 Diabetic Patients with Diabetic Retinopathy at the Dr. Sardjito General Hospital Yogyakarta - Agustina Welhelmina Djuma; S. Sunarti; Pramudji Hastuti (Indonesian Journal of Biotechnology, 2012)
Receptor of advanced glycation endproduct (RAGE) plays an important role in the pathogenesis of diabetic vascular complications, such as diabetic retinopathy. The interaction between the RAGE and advanced glycation end product (AGE) leads to oxidative stress and could result in cellular activation and infl ammation. The production of AGE occurs normally during aging but it increases in hyperglycemia condition. The objective of this research was to investigate the association between -429 T/C and -374 T/A polymorphisms in RAGE gene with the risk of diabetic retinopathy (DR) of type 2 diabetic patients in Javanese population. This was a case control study which consisted of 40 type 2 diabetic patients with DR as case subjects and 40 type 2 diabetic patients without DR (NDR) as control subjects. Genotyping of polymorphism was performed by PCR-RFLP. Chi-square test and odds ratio models were used to evaluate the association of both polymorphisms and DR risk and to examine 2-SNP haplotype of -429 T/C and -374 T/A polymorphisms in RAGE gene on DR. The genotype frequencies of -429 T/C polymorphism in RAGE gene in DR subjects were TT = 72.5% and TC/CC = 27.5%; while in NDR subjects were TT = 80% and TC/ CC = 20%, with p = 0.431. The allele frequencies of -429 T/C polymorphism in DR subjects were T = 83.7% and C= 16.3%, while in NDR subjects were T = 87.5% and C = 12.5%, with p = 0.499. The genotype frequencies of -374T/A polymorphism in RAGE gene in DR subjects were TT = 67.5%, TA = 32.5% while in NDR subjects were TT =82.5%, TA = 17.5%, with p = 0.121. In DR subjects, the frequencies of T and A were 83.7% and16.3%, while in NDR subjects the frequencies of T and A were 91.2 % and 8.8%, with p = 0.151. Odds ratios of -429 T/C polymorphism were 1.52 (95% CI = 0.54 – 4.29) for TC/CC genotype and 1.358 (95% CI = 0.56 – 3.31) for C allele. Odds ratios of -374 T/A polymorphism were 2.27 (95% CI = 0.79 – 6.49) for TA genotype and 2.02 (95% CI = 0.76 – 5.37) for A allele. χ2-value for 2-SNP haplotype was p = 0.127. The -374 T/A polymorphism in RAGE gene was a stronger risk factor of DR than -429 T/C polymorphism in RAGE gene. There were not signifi cantly different of frequencies of genotypes, allele, and two-SNP haplotype of -429 T/C and -374 T/A polymorphisms in RAGE gene between DR subjects and NDR subjects.